Peran Keluarga yang Mempengaruhi Perilaku Seks Bebas pada Remaja (Systematic Review): The Role of Family Influencing Free Sexual Behavior in Adolescents (Systematic Review) - Dinar Eka Muktianasari; Yuni Ginarsih; Rijanto (Gema Bidan Indonesia, 2021)
Background: Adolescence is a time of transition from children to adulthood, during which time, manychanges occur. Teenagers not ready to accept these changes will cause negative things such as free sex.Method:Based on data from the Indonesian Child Protection Commission, 32% of adolescents aged 14 to 18 in major cities in Indonesia have had sex. Families need to apply their roles well to prevent theoccurrence of free sex in adolescents. This research uses a systematic type of research review. The search was carried out in several electronic data bases in the last 5 years which were published both in English and Indonesian. Results : The results of the review show 9 journals that have an influence with the occurrence of free sex in adolescents with low levels of communication, support, supervision and education and family environments that have a lot of conflict. In the review results also found 2 journals that have an effect on one sex only because the research use disbasedon differences in family roles seen from a gender perspective and the presence of other factors so that the review results obtainedthe role of family has an influence on free sex behavior in adolescents. Conclussion : One of the ways to improve therole of the family is to provide access to information and education in order to improve the character quality of adolescents. Keywords : family role, behavior, freesex, adolescents.